2011
DOI: 10.14214/sf.104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of latitude, season and needle-age on the mycota of Scots pine (Pinus sylvestris) in Finland

Abstract: The seasonal and latitudinal influences on the diversity and abundance of mycota of Pinus sylvestris needles were investigated. A sample of 1620 needles resulted in a total of 3868 fungal isolates, which were assigned to 68 operational taxonomic units (OTUs). The majority of these OTUs (65%) belong to Ascomycota and only 0.03% was grouped as Basidiomycota. The dominant and most frequently isolated OTU was Hormonema dematioides. Other wellknown species with a saprotrophic nutritional mode such as Lophodermium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 85 publications
3
49
2
Order By: Relevance
“…The majority of fungal species tended to appear in very low numbers (singletons and doubletons) while only few taxa were really frequent, as phoresy index values suggested (Table 2). This phenomenon seems to be common everywhere in nature, and it has been broadly reported either in fungi-insect associations or fungal endophytes [48][49][50]. Although pine host species were different among plots, the Sorensen index indicated a high-intermediate similarity in the mycobiota among plots (I = 0.70).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The majority of fungal species tended to appear in very low numbers (singletons and doubletons) while only few taxa were really frequent, as phoresy index values suggested (Table 2). This phenomenon seems to be common everywhere in nature, and it has been broadly reported either in fungi-insect associations or fungal endophytes [48][49][50]. Although pine host species were different among plots, the Sorensen index indicated a high-intermediate similarity in the mycobiota among plots (I = 0.70).…”
Section: Discussionmentioning
confidence: 85%
“…This fungus was a dominant species in the studied community and showed the highest and most significant value of PI. S. polyspora has been reported as very frequent species carried by insects [57,58] as well as an endophyte and a saprophyte [48,66,67]. Therefore, this fungus has been considered a primary coloniser of woodlands litter [68].…”
Section: Discussionmentioning
confidence: 99%
“…As described in previous studies (Ganley & Newcombe 2006;Koukol et al 2012;Terhonen et al 2011), the Pinus phyllosphere (i.e. the environment for microorganisms on and below the needle surface) is a rich and varied microbial community.…”
Section: Introductionmentioning
confidence: 75%
“…The fungi identified in this study that have already been described as Scots pine endophytes in earlier reports were Alternaria alternata, A. infectoria, A. tenuissima, Aspergillus fumigatus, Aureobasidium pullulans, Beauveria bassiana, Fimatariella rabenhorstii, Fusarium verticillioides, Geomyces sp., H. lixii, H. viridescens, Hormonema dematioides, Lophodermium conigenum, P. herbarum, P. macrostoma, Sarocladium strictum, Sordaria fimicola, Penicillium glabrum, P. minioluteum, Sarea resinae, Trichoderma atroviride, T. viride, and Xylaria sp (Cooke 1973;Carroll et al 1977;Russo & Bradley 1979;Diwani & Millar 1987;Land et al 1993;Kub atov a 2000;Anderson et al 2003;Pirttil€ a et al 2003;Lygis et al 2004;Kwasna 2008;Zamora et al 2008;Giordano et al 2009;Per soh et al 2010;Menkis & Vasaitis 2011;Terhonen et al 2011), while the following species have been found in other pine species: Daldinia fissa, Nigrospora oryzae, Ophiostoma nigrocarpum, Penicillium melinii, P. polonicum, Pezicula eucrita (Smith 1965;Carroll & Carroll 1978;Kowalski & Zych 2002;Guo et al 2003;Kim et al 2005;Wang et al 2005;Zamora et al 2008;Botella & Diez 2010;Kowalski & Andruch 2011).…”
Section: Discussionmentioning
confidence: 99%